Study of sound absorption by using acoustic impedance tube - Wai, Yan Oo (2011)
Sound absorption is a basic principle in controlling noise and sound absorption coefficient is a major factor in designing noise control components. This report presents an experimental study on sound absorption coefficient of micro perforated plate by using two-microphone impedance tube. In this experiment, effect of air cavity gap, effect of gap between two micro perforated plates and effect of perforated plate thickness on sound absorption coefficient are examined. The results show that the air cavity gap does have a magnificent affect on sound absorption coefficient. The details of micro perforated plate samples, experimental procedures and results analysis are presented in this report.